Improvement of Chronic Idiopathic Urticaria With Levothyroxine: A Case Report and Review of Literature - Shahbaz, Amir (Cureus, 2018)
There is an increased association between chronic urticaria (CU) and thyroid autoantibodies. We presented a case of a patient suffering from CU and newly diagnosed Hashimoto’s thyroiditis in which levothyroxine therapy completely resolved the symptoms of urticaria. A 58-year-old female with a past medical history of recurrent urticaria presented with complaints of fatigue and weight gain. Laboratory investigations showed a high thyroid stimulating hormone (TSH) level and a low free thyroxine (T4) level. She had elevated levels of antithyroid peroxidase (anti-TPO) and anti-thyroglobulin antibodies (anti-TG). She was diagnosed as a case of Hashimoto's thyroiditis and started on levothyroxine therapy. She noticed that her uncontrolled recurrent urticaria started to get better and after a few months of therapy, she stopped taking her topical ointments and antihistamines. The reason for the association between positive serological tests for thyroid autoimmunity and CU is unclear. The resolution of chronic urticaria with levothyroxine in our patient with Hashimoto's thyroiditis suggests a common underlying mechanism between the two pathologies.